2016
DOI: 10.1097/sap.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Keystone Perforator Island Flap for Closure of Lumbosacral Myelomeningocele Defects

Abstract: Myelomeningocele, also known as spina bifida, is the commonest form of neural tube defect in which both meninges and spinal cord herniate through a large vertebral defect. It may be located at any spinal level; however; lumbosacral involvement is most common. After birth, the closure of spinal lesion is preferably undertaken in the first 48 hours to minimize the risk of injury and central nervous system infection. Relatively small skin defects overlying the dural repair may be directly closed. However, larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…More recently, in a case series of 5 patients, Park et al 5 demonstrated the use of keystone flaps in lumbosacral myelomeningocele repair and concluded that it is an effective, reliable, and durable reconstructive option.…”
mentioning
confidence: 99%
“…More recently, in a case series of 5 patients, Park et al 5 demonstrated the use of keystone flaps in lumbosacral myelomeningocele repair and concluded that it is an effective, reliable, and durable reconstructive option.…”
mentioning
confidence: 99%
“…The special anatomy and anatomic site of this region lead to wounds that are difficult to remedy. The keystone design perforator island flap (KDPIF) has the advantages of simple design, sufficient blood supply from the perforators, and similar color and texture to the surrounding tissue, and having been widely used in clinical practice since it was first introduced . Vacuum‐assisted closure (VAC) effectively reduces secondary necrosis and infection of the wound, induces regeneration of the peripheral tissue, increases the rate of flap survival, and promotes wound healing .…”
Section: Introductionmentioning
confidence: 99%
“…In the lower extremities, it has been used to reconstruct post‐traumatic injuries, such as leg open fractures . It has also been used for repairing lumbosacral defects in newborns with myelomeningocele …”
Section: Introductionmentioning
confidence: 99%
“…9 It has also been used for repairing lumbosacral defects in newborns with myelomeningocele. 10 Khouri et al described its use for the repair of defects after excision of soft tissue tumors in the trunk and limbs. 11 Al-Busaidi et al also described its use in defects that remain after burns.…”
Section: Introductionmentioning
confidence: 99%